2010
DOI: 10.4269/ajtmh.2010.10-0370
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Urinary Aluminum Concentrations in Severely Anemic Geophagous Pregnant Women in the Bas Maroni Region of French Guiana: A Case-Control Study

Abstract: The clays consumed by geophagous individuals contain large quantities of aluminum, a known neurological and hematological toxin. This is the first study to evaluate the risk of aluminum poisoning in geophagous individuals. Blind determinations of plasma and urinary aluminum concentrations were carried out in 98 anemic geophagous pregnant women and 85 non-anemic non-geophagous pregnant women. Aluminum concentrations were significantly higher (P < 0.0001) in the geophagous anemic women than in the controls, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 29 publications
1
5
0
2
Order By: Relevance
“…The mean Al serum level in pregnant women at delivery in our study was 10.1 μg/L with an overall median of 6.79 μg/L, which is above the ATSDR guidance. These results are comparable to the 13.92 ± 14.09 μg/L concentrations of Al in plasma, which were measured in a cohort of pregnant women practicing the ancestral cultural custom of ingestion of earth (geophagy) in French Guiana [ 31 ]. A comparable study measured Al in maternal blood in Japanese women and the Al levels reported were 7.83 μg/L [ 32 ].…”
Section: Discussionsupporting
confidence: 79%
“…The mean Al serum level in pregnant women at delivery in our study was 10.1 μg/L with an overall median of 6.79 μg/L, which is above the ATSDR guidance. These results are comparable to the 13.92 ± 14.09 μg/L concentrations of Al in plasma, which were measured in a cohort of pregnant women practicing the ancestral cultural custom of ingestion of earth (geophagy) in French Guiana [ 31 ]. A comparable study measured Al in maternal blood in Japanese women and the Al levels reported were 7.83 μg/L [ 32 ].…”
Section: Discussionsupporting
confidence: 79%
“…The present paper showed that in French Guiana the incidence of death from congenital malformations of the cardiovascular and neurological system was significantly higher than in mainland France. There are several potential explanations for this high incidence of deaths from congenital malformations: infections during pregnancy [14, 20, 21], exposure to toxic metals [13, 22, 23], fetal alcohol syndrome, diabetes, nutritional deficiencies, social precariousness, preterm birth [8], and endogamy [9, 11]. The policy implications of this observation are that spontaneous abortions, stillbirths, and congenital malformations, should be the focus of specific individual data collection to better describe their nature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, copper has reportedly been linked to genomic instability, which is related to breast cancer in rats [21], whereas cadmium is related to breast cancer in women worldwide [22]. Furthermore, aluminum chloride is being investigated for its potential relationship with neurological, hepatic, bone, and hematological conditions as well as with breast cancer [23][24][25][26][27]. Therefore, we assessed the genotoxic effects of aluminum concentration in Sprague Dawley rats and determined whether a link could be established with N-nitroso-N-methylurea (NMU)-induced breast cancer.…”
Section: Introductionmentioning
confidence: 99%